Var hun from eller sindssyg? Om årsagen til at Margrethe Christensdatter i 1741 begik drab - Reeh, Tine; Hemmingsen, Ralf (Kirkehistoriske Samlinger, 2019)
Denne artikel er en nærlæsning af trykte og utrykte kilder til en mordsag fra 1700-tallet, hvor en kvinde, tilsyneladende uden årsag, dræber et barn. Netop denne sag er blevet fremhævet som et paradigmatisk eksempel på en kategori af mord, der er blevet kaldt selvmordsmord. Sagens materiale bliver i artiklen genlæst og analyseret af henholdsvis en psykiater og en kirkehistoriker med henblik på efterprøvelse af morderens eventuelle bevæggrunde. Årsagen til 1700-tallets såkaldte selvmordsmord er i den seneste forskningslitteratur blevet forbundet med religiøse og særligt luthersk pietistiske opfattelser. Artiklens undersøgelse af, hvorvidt det er muligt i denne sag at identificere religiøse eller psykiatriske årsagsforklaringer, leder imidlertid til en alternativ konklusion. Summary Was she Pious or Mentally Ill? On why Margrethe Christensdatter Committed Murder in 1741? Just before Christmas 1741, the 23-year-old Margrethe Christensdatter drowned the 9-year-old Maren Jensdatter in the canals of Copenhagen. The murder has been used as a paradigmatic example of a so-called suicide murder, where the murderers commit the crime in order to end their own life through a public execution. This article re-reads the sources for Christensdatter’s case in order to re-examine the assumptions and on the basis of church history and psychiatry find alternative explanations. The reading of the sources from the legal system reveals that Christensdatter showed signs of mental illness previous to the murder, and that she experienced a dream that drove her to commit murder. After the deed she did not turn herself in at first but wandered restless, confused and depressed around town, and it was not until she heard the child listed missing that she contacted the authorities. There are no signs of a death wish from Christensdatter in her case, and she shows no special preoccupation with religious questions at all. She denies having committed the murder or taken responsibility for it in order to take her own life. The introduction of Satan in the protocols comes from her attorney in an attempt to defend her actions. She claims to be content with the death sentence by use of a standard formula that may mitigate the way of punishment. The article then examines the memoirs of the theologian Henrik Gerner (1701-1786). Gerner mentions a case that may be Christensdatter’s. But the Gerner narration is first and foremost a defense for his own Moravian inspiration and theological minority opinions. He uses the story of a theologically bewildered female murderer to demonstrate that faith in Jesus and the mercy of God is the only way to salvation, and that Gerner’s theology can thus be proven true. Gerner’s text is not trustworthy as to the religious motives of Christensdatter and only reveal little reliable information on the case. The article then discuss the thesis of Tyge Krogh, who sees Christensdatter’s case as a typical example from an assumed epidemic of suicide murders in the heyday of pietism. Krogh’s and other studies point to religious beliefs and in particular Lutheranism as the cause of the phenomenon. The article points out that there are several inconsistencies and weakness in this interpretation and that modern psychiatry can provide new nuances and alternatives in our understanding of these cases. In conclusion, the re-examination of the sources in Christensdatter’s case points in the direction of a mental illness rather than a wish to terminate her own life grounded in Lutheran pietistic beliefs as the background for her murder.